Exploring the Cultural Domain of Hausa Colour Terms - Dr. Danladi Bello Dogondaji (NUST Journal of Social Sciences and Humanities)
The study of colour terms has been an interesting phenomenon in linguistics. The power of colour terms to name and classify things, animals and persons in purely traditional way cannot be over emphasized across cultures. Of course, there are universal tendencies on the nature of colour naming across languages but such universality does not apply to the socio-cultural aspect of all societies. This was supported by Durbin (1971), Casson (1994, 1997), Downman 92003), Bature (2005), Danladi (2010) and Aujara (2021) who believed that the size of colour vocabulary is certainly a measure of its cultural complexity, the smaller the vocabulary, the simpler the society. Hence, this paper examines the socio-cultural domain of colours terms in Hausa societies. Hausa is a member of Afro- Asiatic family and is estimated to have about 1 billion L1 users according to ethnologue .com. Purposeful Random Sampling and survey method were used and 160 research subjects were selected from the speakers of Hausa language in Sokoto state to source data for the study. The findings, from 154 respondents, reveal that colour is very significant to Hausa culture as it cut across every aspect of socio-cultural, economic, political and religious angles of a typical Hausa social group. It names and classifies traditional cloths and domestic animals on one hand and describes/classifies people or race on the other. The paper also reveals that colour terms are used in rituals and traditional epithet of Hausa society. Hence, it concludes that colour is an indispensable tool for expressing deep thought, ideas and powerful emotions in purely traditional Hausa way.